Sermon-based Messaging to Foster Social Cohesion in Conflict-affected Communities in Mindanao - Mano-Pelin, Jairah Jay (Journal of Interdisciplinary Perspectives, 2025)
Mindanao has faced decades of conflict driven by cultural, religious, and historical complexities. While secular peacebuilding has provided structural solutions, a gap remains in addressing the spiritual dimensions of reconciliation. This study employed a qualitative, multiple-case study approach, incorporating thematic content analysis of sermons and interviews with three Evangelical pastors serving in a Muslim-majority area, an Indigenous community, and a post-conflict barangay. The findings revealed that pastors used biblical storytelling, biblical exposition, and personal testimony as rhetorical strategies to promote unity. Sermons were adapted to address displacement, poverty, and trauma, consistently emphasizing forgiveness, humility, reconciliation, and peace as biblical imperatives. Pastors, however, faced challenges such as pride, mistrust, fear of retaliation, and perceptions of bias. Despite these obstacles, sermons often led to visible acts of repentance, forgiveness, reconciliation, and stronger communal bonds. The study suggests that sermon-based messaging can inform faith-integrated peacebuilding policies in similar conflict zones in building inclusive and sustainable peace.